2020
DOI: 10.1186/s13033-020-00412-4
|View full text |Cite
|
Sign up to set email alerts
|

Measures of depression, generalized anxiety, and posttraumatic stress disorders amongst Yazidi female survivors of ISIS slavery and violence

Abstract: Background In 2014 the Islamic State of Iraq and Syria (ISIS) undertook a systematic and deliberate campaign against minority groups and non-Sunni Muslim communities. Amongst some of the greatest atrocities were those targeted towards Yazidi communities and in particular their women. The mental health outcomes of those women held in captivity requires investigation. This study sought to examine and compare levels of general psychological distress, depression, generalized anxiety, posttraumatic stress disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…“knowledge about mental disorders that are associated with their recognition, management and prevention” [ 29 ]. These findings are consistent with other studies demonstrating the benefits of culturally-tailored mental health promotion and mental health literacy training on the wellbeing and mental health literacy of members of the Arabic-speaking community in Sydney [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…“knowledge about mental disorders that are associated with their recognition, management and prevention” [ 29 ]. These findings are consistent with other studies demonstrating the benefits of culturally-tailored mental health promotion and mental health literacy training on the wellbeing and mental health literacy of members of the Arabic-speaking community in Sydney [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, by visiting common public places, this modality also attempted to address the issue of selection bias, particularly when past internet-based surveys have been oversubscribed by younger participants. Finally, we utilized well-validated measures of depression and anxiety that have been previously used in the Kurdistan region [ 59 ] to identify postulated cases using published cut-off. Nonetheless, both the PHQ-9 and GAD-7 are self-report and not diagnostic interview tools, precluding clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 416 Yazidi women and girls (65 of whom had survived sexual enslavement) in IDP camps in the KRI, more than 80% and almost all survivors who had experienced enslavement fulfilled criteria for PTSD (Ibrahim et al, 2018). It has been shown that formerly enslaved Yazidi females suffer from higher prevalence of mental stress (97.1%), PTSD (90.6%), suicidal ideation (38.1%), depression (36.7%), and general anxiety symptoms (37.4%) (Taha and Slewa-Younan, 2020). Among those who had been sexually abused, very high prevalence rates of mental stress of 50.9% for complex PTSD and 20% for PTSD were found 10.3389/fpsyg.2023.1074283 Frontiers in Psychology 03 frontiersin.org (Hoffman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%